2017
DOI: 10.1097/qai.0000000000001398
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Couple HIV Testing and Counseling on Consistent Condom Use Among Pregnant Women and Their Male Partners: An Observational Study

Abstract: Background In sub-Saharan Africa couple HIV testing and counseling (CHTC) has been associated with substantial increases in safe sex, especially when at least one partner is HIV-infected. However, this relationship has not been characterized in an Option B+ context. Setting The study was conducted at the antenatal clinic at Bwaila District Hospital in Lilongwe, Malawi in 2016 under an Option B+ program. Methods Ninety heterosexual couples with an HIV-infected pregnant woman (female-positive couples) and 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 41 publications
1
22
2
Order By: Relevance
“…At the same time, FSWs in Uganda believe that the vast majority of their clients are living with HIV and thus may be unconcerned about infecting their clients. These reasons may explain why the results from our study among FSWs differ from the results of studies in general populations, which have mostly found that knowledge of HIV‐positive status is associated with a reduction in HIV risk‐related sexual behaviours .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…At the same time, FSWs in Uganda believe that the vast majority of their clients are living with HIV and thus may be unconcerned about infecting their clients. These reasons may explain why the results from our study among FSWs differ from the results of studies in general populations, which have mostly found that knowledge of HIV‐positive status is associated with a reduction in HIV risk‐related sexual behaviours .…”
Section: Discussioncontrasting
confidence: 99%
“…In urban Uganda, knowledge of HIV status was not associated with FSWs’ number of clients on an average working night, but knowledge of HIV‐negative status was significantly associated with an increase in FSWs’ consistent condom use with clients. This latter finding is different from most of the previous studies on knowledge of HIV status and sexual behaviour, which took place among members of the general population and found that knowledge of HIV‐negative status was not associated with HIV risk‐related sexual behaviours . It is particularly encouraging that FSWs in this setting who learn that they are HIV‐negative forgo the opportunity to make almost triple the amount of money for a sex act without a condom compared to a sex act with a condom – presumably to protect themselves from HIV acquisition.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…increases uptake of HIV prevention and care services and identification of HIV sero-discordant couples [6][7][8]. The 'Primary HIV Prevention among Pregnant and Lactating Ugandan Women' (PRIMAL) randomized controlled trial (RCT) assessed the effect of the enhanced counseling component effects of an extended repeat HIV testing and enhanced counseling (ERHTEC) intervention on 410 HIVnegative pregnant and lactating women and 205 of their male partners compared to an equal number of controls on risk reduction behavior and the risk of STI and HIV acquisition by these mothers during late pregnancy and throughout the breastfeeding period [9].…”
Section: Studies In East and Southern Africa Have Shown That Couple Hmentioning
confidence: 99%